Sodium niobate-based ceramic substituted and modified by magnetic elements and preparation method of sodium niobate-based ceramic

By introducing magnetic elements to replace modified sodium niobate-based ceramic materials, controlling the amount of ion substitution of A/B positions, the problems of insufficient energy storage density and high dielectric loss of sodium niobate-based materials are solved, and high energy storage density and High efficiency energy storage performance.

CN119462146APending Publication Date: 2025-02-18SHIHEZI UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411568897.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The application of existing sodium niobate-based materials in high-energy density energy storage devices has problems such as insufficient energy storage density, high dielectric loss, and poor performance stability under high temperature conditions.

Method used

By introducing magnetic elements to replace the modified sodium niobate-based ceramic material, the chemical composition formula is (1-x)NaNbO3-0.8xLaFeO3-0.2xSr(Fe0.5Nb0.5)O3, 0.08≤x≤0.14, control A/B Position ion replacement amount to improve dielectric properties and ferroelectric relaxation.

Benefits of technology

The energy storage density and energy storage efficiency of sodium niobate-based ceramic materials have been significantly improved, and their reliability and stability in practical applications have been enhanced, and the problems of low energy storage density and efficiency of pure sodium niobate ceramic materials have been overcome.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462146A_ABST
    Figure CN119462146A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic element substituted and modified sodium niobate-based ceramic and a preparation method thereof. The chemical composition is (1-x) NaNbO3-0. 8xLaFeO3-0. 2xSr (Fe0. 5Nb0. 5) O3, wherein x is more than or equal to 0.08 and less than or equal to 0.14. The preparation method comprises the following steps: proportioning the raw materials NaHCO3, Nb2O5, La2O3, Fe and SrCO3 according to the chemical composition; pre-sintering and ball-milling to obtain raw material powder; and pressing the powder into sheets by using a mold, and sintering at 1250-1300 DEG C for 3 hours to obtain the magnetic element substituted and modified sodium niobate-based ceramic. The preparation method disclosed by the invention is simple in steps and high in repeatability. The prepared solid solution ceramic material has high energy storage density of 3.276 J / cm < 3 > and high energy storage efficiency of 80.7%, and is a lead-free ceramic material with a good commercial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of energy storage materials, and in particular to a sodium niobate-based ceramic material modified by substitution of magnetic elements and a preparation method thereof. Background Art

[0002] With the intensification of the global energy crisis and the prominence of environmental pollution problems, the rapid development of green and environmentally friendly renewable energy and efficient energy storage technology has become a key means to meet the current energy challenges. Traditional fossil energy storage and conversion methods are gradually replaced by renewable energy, but renewable energy such as solar energy and wind energy require efficient energy storage systems to balance supply and demand due to their instability and intermittent characteristics. Among the existing energy storage materials, lead-based ferroelectric materials (such as lead zirconate titanate, PZT) have shown excellent electrical properties in energy storage devices and are widely used in capacitors and piezoelectric devices. However, lead-based materials do not meet the current global requirements for environmental protection and sustainable development because they contain environmentally harmful lead elements. The toxicity of lead not only affects the natural ecological environment, but also poses a potential threat to human health. Therefore, finding a lead-free energy storage material to replace lead-based materials has become a key direction of scientific research and technological development.

[0003] Among the many lead-free materials, sodium niobate (NaNbO 3 )-based materials have great application potential in the field of energy storage due to their perovskite structure. Sodium niobate materials not only have ferroelectricity and high dielectric constant similar to lead-based materials, but also have good thermal stability and environmental friendliness, which is in line with the development trend of green energy storage technology. Studies have shown that the dielectric properties and energy storage efficiency of sodium niobate-based materials can be significantly improved by doping with other elements (such as barium, calcium, strontium, etc.) or by changing the preparation process.

[0004] However, the application of sodium niobate-based materials in high energy density energy storage devices still faces certain technical bottlenecks, mainly manifested in its insufficient energy storage density, high dielectric loss and poor performance stability under high temperature conditions. In addition, although certain progress has been made in the research of sodium niobate-based materials, its cycle stability in practical applications, controllability of processing technology and integrated compatibility with existing energy storage devices are still important difficulties in technical development. Therefore, it is urgent to develop an improved method that can further optimize the energy storage performance of sodium niobate-based materials, so as to improve its energy density, reduce dielectric loss and enhance its reliability and stability in practical applications. Summary of the invention

[0005] The purpose of the present invention is to provide a sodium niobate-based ceramic material modified by substitution of magnetic elements and a preparation method thereof, so as to overcome the problem of insufficient energy storage performance of sodium niobate-based materials in the prior art and to improve their energy storage density and energy storage efficiency.

[0006] To achieve the above object, the present invention provides a sodium niobate-based ceramic material modified by substitution of magnetic elements, the chemical composition formula of which is: (1-x)NaNbO 3 -0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3, 0.08≤x≤0.14.

[0007] The preparation method of the above sodium niobate-based ceramic material is as follows:

[0008] (1) Ingredients

[0009] According to (1-x)NaNbO 3 -0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3 The raw materials NaHCO and 3 , Nb 2 O 5 ,La 2 O 3 ,Fe,SrCO 3 .

[0010] (2) Pre-burning

[0011] The weighed raw material mixture was placed in an alumina crucible, heated to 120°C in a muffle furnace and kept warm for 60 min to dry the raw material mixture, then heated to 500°C and then to 860°C, kept at 860°C for 180 min, and then naturally cooled to room temperature.

[0012] (3) Ball milling

[0013] The pre-calcined powder was placed in a ball mill, with agate balls as grinding balls and anhydrous ethanol as the ball milling medium, and after mixed ball milling for 24 hours, the agate balls and slurry were separated, and the slurry was dried. The dried slurry was then ground in a mortar to obtain a raw material powder.

[0014] (4) Tableting

[0015] The raw material powder was pressed into a disc with a diameter of about 10 mm using a grinding tool at a pressure of 8 MPa.

[0016] (5) Sintering

[0017] The wafer is heated at a rate of 5°C / min, kept at 1250-1300°C for 180 minutes, and then naturally cooled to room temperature to obtain a sodium niobate-based ceramic material modified by substitution of magnetic elements.

[0018] (6) Polishing

[0019] The sintered ceramics are ground with sandpaper to a thickness of 0.12 to 0.15 mm, then polished with metallographic sandpaper and wiped clean with alcohol.

[0020] Furthermore, in step 1, the purity of the raw materials used is respectively NaHCO 3 (99.8%), Nb 2 O 5 (99%), La 2 O 3 (99.9%), Fe(98.35%), SrCO 3 (99%).

[0021] Furthermore, in step 2, the pre-calcination heating rate is 5°C / min.

[0022] Further, in step 6, when the sample thickness is greater than 0.35 mm, it is polished with 600-mesh sandpaper; when the thickness is between 0.20 mm and 0.35 mm, it is polished with 1200-mesh sandpaper; when the thickness is between 0.15 mm and 0.20 mm, it is polished with 1200-mesh sandpaper, and finally polished with metallographic sandpaper.

[0023] Material of the present invention (1-x) NaNbO 3 -0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3 (0.08≤x≤0.14), by controlling the amount of ion substitution at the A / B position, the dielectric properties and ferroelectric relaxation degree of the sodium niobate-based ceramic material are improved, so that the maximum polarization strength of the material is increased and the coercive field strength is reduced, thereby simultaneously improving the energy storage density and energy storage efficiency of the sodium niobate-based ceramic material. When x=0.12, the sample can obtain the best energy storage characteristics. Therefore, the present invention can change the energy storage characteristics of the material by simultaneously substituting the A / B position and controlling the amount of substitution, thereby overcoming the problems of low energy storage density and low efficiency of pure sodium niobate ceramic materials.

[0024] The preparation method of the present invention has simple steps and high repeatability. The prepared solid solution ceramic material also has a high energy storage density of 3.276 J / cm 3 And the energy storage efficiency is 80.7%, which can solve the problems of low energy storage density and efficiency of pure sodium niobate ceramic materials. It is a lead-free ceramic material with great commercial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The (1-x)NaNbO provided in Examples 1 to 4 of the present invention 3-0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3 X-ray diffraction spectrum of ceramic material surface.

[0026] Figure 2 The (1-x)NaNbO provided in Examples 1 to 4 of the present invention 3 -0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3 Scanning electron micrograph of the surface of a ceramic material.

[0027] Figure 3 The (1-x)NaNbO provided in Examples 1 to 4 of the present invention 3 -0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3 Hysteresis loop diagram of ceramic at room temperature. DETAILED DESCRIPTION

[0028] The above contents of the present invention are further described in detail below through embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Embodiment 1: This embodiment 1 discloses a ceramic material, whose chemical formula is:

[0030] (1-x)NaNbO 3 -0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3 , wherein x=0.08. The preparation method thereof comprises the following steps:

[0031] (1) Ingredients

[0032] According to (1-x)NaNbO 3 -0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3, The raw materials NaHCO and 3 (purity 99.8%), Nb 2O 5 (purity 99%), La 2 O 3 (purity 99.9%), Fe (purity 98.35%), SrCO 3 (Purity 99%).

[0033] (2) Pre-burning

[0034] The weighed raw material mixture was placed in an alumina crucible and heated to 120°C in a muffle furnace at a heating rate of 5°C / min. o C for 60 min to dry the raw material mixture, then continue to heat up to 500°C at a heating rate of 5°C / min and then to 860°C, and keep it at 860°C for 180 min and then naturally cool to room temperature.

[0035] (3) Ball milling

[0036] The pre-calcined powder was placed in a ball mill, with agate balls as grinding balls and anhydrous ethanol as the ball milling medium, and after mixed ball milling for 24 hours, the agate balls and slurry were separated, and the slurry was dried. The dried slurry was then ground in a mortar to obtain a raw material powder.

[0037] (4) Tableting

[0038] The raw material powder was pressed into a disc with a diameter of about 10 mm using a grinding tool at a pressure of 8 MPa.

[0039] (5) Sintering

[0040] The wafer is heated at a rate of 5°C / min, kept at 1250-1300°C for 180 minutes, and then naturally cooled to room temperature to obtain a sodium niobate-based ceramic material modified by substitution of magnetic elements.

[0041] (6) Polishing

[0042] The sintered ceramics are ground to a thickness of 0.12-0.15 mm using 600, 1200, and 2000 grit sandpaper, then polished using metallographic sandpaper and wiped clean with alcohol.

[0043] The prepared sodium niobate-based ceramic material was subjected to X-ray diffraction test, and its surface X-ray diffraction spectrum was as follows: Figure 1 shown.

[0044] The prepared sodium niobate-based ceramic material was subjected to a high-resolution field emission electron scanning microscope, and its natural surface SEM image was as follows: Figure 2 shown.

[0045] The polished sodium niobate-based ceramic sample was coated with low-temperature silver paste on both sides and placed in a vacuum drying oven at 100°C to be dried and silver electrodes were applied. Then, its ferroelectric properties were tested at room temperature at a frequency of 10 Hz. The hysteresis loop of the ceramic material of this embodiment measured at room temperature is shown in the figure below. Figure 3 The energy storage characteristics of the ceramic material of this embodiment at room temperature are shown in Table 1.

[0046] Embodiment 2: This embodiment discloses a ceramic material, whose chemical composition formula is:

[0047] (1-x)NaNbO 3 -0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3 , wherein x = 0.10. The preparation method thereof is repeated in the above-mentioned proportions in Example 1 to obtain the sodium niobate-based ceramic material modified by substitution of the magnetic element. The natural surface SEM image of the ceramic material of this example is as follows Figure 2 The hysteresis loop of the ceramic material of this embodiment measured at room temperature is shown in Figure 3 The energy storage characteristics of the ceramic material of this embodiment at room temperature are shown in Table 1.

[0048] Embodiment 3: This embodiment discloses a ceramic material, whose chemical composition formula is:

[0049] (1-x)NaNbO 3 -0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3 , wherein x = 0.12. The preparation method thereof is repeated in the above-mentioned proportions in Example 1 to obtain the sodium niobate-based ceramic material modified by substitution of magnetic elements. The natural surface SEM image of the ceramic material of this example is as follows Figure 2 The hysteresis loop of the ceramic material of this embodiment measured at room temperature is shown in Figure 3 The energy storage characteristics of the ceramic material of this embodiment at room temperature are shown in Table 1.

[0050] Embodiment 4: This embodiment discloses a ceramic material, whose chemical composition formula is:

[0051] (1-x)NaNbO 3 -0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3, wherein x = 0.14. The preparation method thereof is repeated in the above-mentioned proportions in Example 1 to obtain the sodium niobate-based ceramic material modified by substitution of magnetic elements. The natural surface SEM image of the ceramic material of this example is as follows Figure 2 The hysteresis loop of the ceramic material of this embodiment measured at room temperature is shown in Figure 3 The energy storage characteristics of the ceramic material of this embodiment at room temperature are shown in Table 1.

[0052] Embodiment 5: This embodiment discloses a ceramic material, whose chemical composition formula is:

[0053] (1-x)NaNbO3-0.8xLaFeO3-0.2xSr(Fe0.5Nb0.5)O3, wherein x=0. The preparation method thereof is repeated in the above-mentioned proportions in the preparation method of Example 1. The energy storage properties of the ceramic material of this example at room temperature are shown in Table 1.

[0054] The energy storage properties of the materials prepared by the above preparation method using five different ratios in Example 1, Example 2, Example 3, Example 4 and Example 5 are shown in Table 1:

[0055]

[0056]

[0057] Table 1 Energy storage characteristics of materials in various examples

[0058] As shown in Table 1, as the amount of substitution increases, the energy storage density of the ceramic material of the present invention first decreases, then increases, and then decreases, while the energy storage efficiency first increases and then decreases. In Example 3, when x = 0.12, the energy storage density is 3.276 J / cm 3 and energy storage efficiency of 80.7%, which can meet the requirements of energy storage ceramic dielectric materials in practical applications that require both high energy storage density and energy storage efficiency. This shows that (1-x)NaNbO 3 -0.8xLaFeO 3 -0.2xSr(Fe 0.5 Nb 0.5 ) 3 Ceramics is a lead-free candidate material with great application potential.

[0059] Depend on Figure 1 It can be seen that all samples prepared in this example show a pure perovskite structure without a second phase. Figure 2 It can be seen that all samples prepared in this example have a uniform and dense structure. Figure 3 It can be seen that the sample with x=0.12 in Example 3 has a higher maximum polarization intensity and is relatively thin, with better energy storage properties, overcoming the shortcomings of the energy storage properties of pure sodium niobate ceramic materials.

[0060] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the claims of the present invention still fall within the scope covered by the invention.

Claims

1. A sodium niobate-based ceramic modified by substitution of magnetic elements, characterized in that: The chemical formula is: (1-x)NaNbO3-0.8xLaFeO3-0.2xSr(Fe 0.5 Nb 0.5 )O3, wherein 0.08≤x≤0.14; the energy storage density of the ceramic material is 1.664J / cm 3 -3.276J / cm 3 , the energy storage efficiency is 62.5%-80.7%.

2. A method for preparing the sodium niobate-based ceramic modified by substitution of magnetic elements as claimed in claim 1, characterized in that: It consists of the following steps: (1) Ingredients According to (1-x)NaNbO3-0.8xLaFeO3-0.2xSr(Fe 0.5 Nb 0.5 )O3 (0.08≤x≤0.14) using a high-precision electronic balance to weigh the raw materials NaHCO3, Nb2O5, La2O3, Fe, and SrCO3 respectively. (2) Pre-burning The weighed raw material mixture was placed in an alumina crucible, heated to 120°C in a muffle furnace and kept warm for 60 min to dry the raw material mixture, then heated to 500°C and then to 860°C, kept at 860°C for 180 min, and then naturally cooled to room temperature. (3) Ball milling The pre-calcined powder was placed in a ball mill, with agate balls as grinding balls and anhydrous ethanol as the ball milling medium, and after mixed ball milling for 24 hours, the agate balls and slurry were separated, and the slurry was dried. The dried slurry was then ground in a mortar to obtain a raw material powder. (4) Tableting The raw material powder was pressed into a disc with a diameter of about 10 mm using a grinding tool at a pressure of 8 MPa. (5) Sintering The wafer is heated at a rate of 5°C / min, kept at 1250-1300°C for 180 minutes, and then naturally cooled to room temperature to obtain a sodium niobate-based ceramic material modified by substitution of magnetic elements. (6) Polishing The sintered ceramics are ground with sandpaper to a thickness of 0.12 to 0.15 mm, then polished with metallographic sandpaper and wiped clean with alcohol.

3. The method for preparing the sodium niobate-based ceramic modified by substitution of magnetic elements according to claim 2, characterized in that: In step (1), the purities of the raw materials used are NaHCO3 (99.8%), Nb2O5 (99%), La2O3 (99.9%), Fe (98.35%), and SrCO3 (99%).

4. The method for preparing the sodium niobate-based ceramic modified by substitution of magnetic elements according to claim 2, characterized in that: In step (2), the pre-calcination heating rate is 5°C / min.

5. The method for preparing the sodium niobate-based ceramic modified by substitution of magnetic elements according to claim 2, characterized in that: In step (6), when the sample thickness is greater than 0.35 mm, it is polished with 600-mesh sandpaper; when the thickness is between 0.20 mm and 0.35 mm, it is polished with 1200-mesh sandpaper; when the thickness is between 0.15 mm and 0.20 mm, it is polished with 1200-mesh sandpaper, and finally polished with metallographic sandpaper.

Citation Information

Patent Citations

  • Preparation method of niobate solid solution material

    CN105174948A

  • Lanthanum oxide doped and modified potassium-sodium niobate-based transparent ceramic and preparation method thereof

    CN111302798A

  • Lead-free relaxor ferroelectric ceramic material with high energy storage density and preparation method of lead-free relaxor ferroelectric ceramic material

    CN115504784A

  • Piezoelectric ceramic composition

    US20100264354A1

  • Unleaded piezoceramic material of the potassium / sodium / niobate system having a iron / lanthanum doping, method for the production of a component comprising the piezoceramic material and use of the component

    WO2009043652A1